Gastrointestinal inflammation and associated immune activation in schizophrenia - Severance, Emily G.; Khushalani, Sunil; Leweke, F. Markus (Schizophrenia research, 2012)
Immune factors are implicated in normal brain development and in brain disorder pathogenesis. Pathogen infection and food antigen penetration across gastrointestinal barriers are means by which environmental factors might affect immune-related neurodevelopment. Here, we test if gastrointestinal inflammation is associated with schizophrenia and therefore, might contribute to bloodstream entry of potentially neurotropic milk and gluten exorphins and/or immune activation by food antigens. IgG antibodies to Saccharomyces cerevisiae (ASCA, a marker of intestinal inflammation), bovine milk casein, wheat-derived gluten, and 6 infectious agents were assayed. Cohort 1 included 193 with non-recent onset schizophrenia, 67 with recent onset schizophrenia and 207 non-psychiatric controls. Cohort 2 included 103 with first episode schizophrenia, 40 of whom were antipsychotic-naïve. ASCA markers were significantly elevated and correlated with food antigen antibodies in recent onset and non-recent onset schizophrenia compared to controls (p≤0.00001-0.004) and in unmedicated individuals with first episode schizophrenia compared to those receiving antipsychotics (p≤0.05-0.01). Elevated ASCA levels were especially evident in non-recent onset females (p≤0.009), recent onset males (p≤0.01) and in antipsychotic-naïve males (p≤0.03). Anti-food antigen antibodies were correlated to antibodies against Toxoplasma gondii, an intestinally-infectious pathogen, particularly in males with recent onset schizophrenia (p≤0.002). In conclusion, gastrointestinal inflammation is a relevant pathology in schizophrenia, appears to occur in the absence of but may be modified by antipsychotics, and may link food antigen sensitivity and microbial infection as sources of immune activation in mental illness.